Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ana.25940
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Growth Trajectories in Fetuses with Congenital Heart Disease

Abstract: Objective Congenital heart disease (CHD) is associated with abnormal brain development in utero. We applied innovative fetal magnetic resonance imaging (MRI) techniques to determine whether reduced fetal cerebral substrate delivery impacts the brain globally, or in a region‐specific pattern. Our novel design included two control groups, one with and the other without a family history of CHD, to explore the contribution of shared genes and/or fetal environment to brain development. Methods From 2014 to 2018, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 52 publications
3
69
0
Order By: Relevance
“…Under tight genetic control, quantitative structural brain features, including brain volume, cortical gyrification, surface area, curvature, and sulcal depth, were strongly correlated with GA and small intersubject variations in typically developing (TD) fetuses ( Rajagopalan et al, 2011 ; Clouchoux et al, 2013 , 2012 ; Hu et al, 2013 ; Wright et al, 2014 ; Namburete et al, 2015 ; Wu et al, 2015 ; Lefèvre et al, 2016 ; Andescavage et al, 2017 ). Moreover, atypical structural features have been more frequently found in fetuses with ventriculomegaly, congenital heart disease, and Down syndrome than in TD fetuses ( Clouchoux et al, 2012 ; Scott et al, 2013 ; Kyriakopoulou et al, 2014 ; Lefèvre et al, 2016 ; Jaimes et al, 2020 ; Tarui et al, 2020 ; Rollins et al, 2021 ; Yun et al, 2021 ). Therefore, prediction of fetal brain age based on structural MRI features may be useful for detecting abnormalities in brain development and the risk of adverse developmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Under tight genetic control, quantitative structural brain features, including brain volume, cortical gyrification, surface area, curvature, and sulcal depth, were strongly correlated with GA and small intersubject variations in typically developing (TD) fetuses ( Rajagopalan et al, 2011 ; Clouchoux et al, 2013 , 2012 ; Hu et al, 2013 ; Wright et al, 2014 ; Namburete et al, 2015 ; Wu et al, 2015 ; Lefèvre et al, 2016 ; Andescavage et al, 2017 ). Moreover, atypical structural features have been more frequently found in fetuses with ventriculomegaly, congenital heart disease, and Down syndrome than in TD fetuses ( Clouchoux et al, 2012 ; Scott et al, 2013 ; Kyriakopoulou et al, 2014 ; Lefèvre et al, 2016 ; Jaimes et al, 2020 ; Tarui et al, 2020 ; Rollins et al, 2021 ; Yun et al, 2021 ). Therefore, prediction of fetal brain age based on structural MRI features may be useful for detecting abnormalities in brain development and the risk of adverse developmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The value of TCD in 56% (10/18 cases) foetuses with VSD was lower than the 3rd centile, and the rates for FOD and BPD were 33% (6/18 cases) and 22% (4/18 cases) separately. Rollins has suggested that the involvement of brain size in the foetus with hypoplastic left heart syndrome or transposition of the great arteries was in a region-specific pattern [ 31 ]. Regional involvement of the brain was also observed in foetuses with single ventricle congenital heart disease [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…in the fetal MRI study of Rollins et al [9] is of importance because this region in the last 16 weeks of gestation is the site of differentiating premyelinating oligodendrocytes (pre-OLs), rapidly growing axons, and late migrating GABAergic neurons.…”
Section: The Involvement Of the Intermediate Zone Shownmentioning
confidence: 99%
“…see earlier).The third region affected in the fetal study ofRollins et al is the ventricular-subventricular zone[9]. These germinative sites in the last 16 weeks of gestation give rise to the GABAergic neurons destined for cerebral cortex, as just described, as well as progenitor cells for pre-OLs.…”
mentioning
confidence: 90%
See 1 more Smart Citation